Blazor WebAssembly full stack web development - Williams, Trevoir (Manning Publications, 2022)
Blazor gives .NET developers the chance to leverage their C# skills and build interactive web UIs. Writing modern web applications with a rich UI can be tedious. So in this course, you will learn Modern Web Development with Blazor and .NET 5 (This course has been updated to show how you can create the project using Visual Studio 2022 and .NET 6.), you will gain the ability to build web applications using Blazor. We will explore: setting up your first Blazor application; how to work with an API and how data binding works; how to create components and integrate JavaScript components. Developing With Blazor - The most popular JavaScript client-side web frameworks have been Angular, React, Vue and others. In this course, we keep it .NET by using Blazor, which is Microsoft's response to that monopoly. Blazor allows you to create a Single Page Application, on top of .NET Core and continue coding in C# (without needing to flip between C# and JavaScript too much). Blazor apps are composed of reusable web UI components implemented using C#, HTML, and CSS. Both client and server code is written in C#, allowing you to share code and libraries. Blazor WebAssembly - Blazor can run your client-side C# code directly in the browser, using WebAssembly (WASM for short). Because it's real .NET running on WebAssembly, you can re-use code and libraries from server-side parts of your application. We will be exploring many intricacies of the Blazor life-cycle, data flow, JavaScript Interoperability and general development activities and nuances. Deploy To Microsoft Azure Cloud - Azure Web App Service is key to deploying the API and Blazor Server Applications. We will also enlist the use of Azure SQL for Database to support our API. When you have finished this course, you will possess the skills and knowledge to build a web application using Blazor.
Online resource; title from title details screen (O'Reilly, viewed January 24, 2023)
Keywords: Microsoft .NET Framework; Web applications; Applications Web; Instructional films; Internet videos; Nonfiction films; Films de formation; Films autres que de fiction; Vidéos sur Internet